2015
DOI: 10.1159/000369277
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam Inhibits Proliferation of Lymph Node Cells Isolated from Rats with Experimental Autoimmune Encephalomyelitis

Abstract: Objective: Experimental autoimmune encephalomyelitis (EAE) is an inflammatory demyelinating disease with similarities to human multiple sclerosis involving peripheral activation of autoreactive T cells which infiltrate the central nervous system and react to self antigens leading to damage. In previous studies, we have demonstrated that treatment with diazepam decreases the incidence and histological signs associated with the disease and diminishes immunological responses. The aim of the present work was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…To what extent the IK Cachannel activity in astrocytes contributes to MDZ mediated regulation of apoptotic changes thus remains to be further determined. Taken together, despite the detail mechanism of MDZ actions on these K + channels being unclear, if similar findings are observed in lymphocytes occurring in cell culture or in vivo to those described herein, the actions of MDZ or its functionally related agents (e.g., diazepam) observed in the present study will result in significant changes in immune reactions [2,[4][5][6]23] Israel). For cell preparations, culture media, fetal bovine serum (FBS), L-glutamine, trypsin/EDTA, penicillin-streptomycin, and amphotericin B were obtained from Invitrogen (Carlsbad, CA, USA).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To what extent the IK Cachannel activity in astrocytes contributes to MDZ mediated regulation of apoptotic changes thus remains to be further determined. Taken together, despite the detail mechanism of MDZ actions on these K + channels being unclear, if similar findings are observed in lymphocytes occurring in cell culture or in vivo to those described herein, the actions of MDZ or its functionally related agents (e.g., diazepam) observed in the present study will result in significant changes in immune reactions [2,[4][5][6]23] Israel). For cell preparations, culture media, fetal bovine serum (FBS), L-glutamine, trypsin/EDTA, penicillin-streptomycin, and amphotericin B were obtained from Invitrogen (Carlsbad, CA, USA).…”
Section: Discussionsupporting
confidence: 81%
“…Assuming that periodical changes in membrane potential of inner mitochondrial membranes may take place [44], the issue of whether blockade of mitochondrial K V 1.3 channels caused by MDZ is responsible for its effects on Bax-K V 1.3 interactions [23,37] is worthy of being investigated. Nonetheless, because of the importance of I K(DR) (i.e., K V 1.3-encoded current) in contributing to functional activities of lymphocytes [19,36], the effects presented herein could provide novel insights into pharmacological or immunological properties of MDZ and other structurally related compounds (e.g., diazepam) [1,2,[4][5][6]9,20,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the goal of this work was to evaluate the ability of DZ to suppress the different phases of the immune responses. We suggest that DZ could affect not only the maturation of APCs and their ability to initiate adaptive responses, but it could also have an effect on the expansion and proliferation of antigen-specific T cells as we have previously shown (12). Therefore, herein we demonstrated that DZ suppressed established inflammatory responses in vitro.…”
Section: Discussionsupporting
confidence: 79%
“…Upregulation of the TSPO is observed in many CNS diseases, and some TSPO ligands are currently under investigation as therapeutic means for promoting neuroprotection, axonal regeneration, and modulating inflammation (6,7). Diazepam (DZ), which is a mixed-type benzodiazepine that can act on both central and peripheral benzodiazepine receptors, has been demonstrated to have an inhibitory effect on T cell function (8)(9)(10)(11)(12). However, the action on professional antigenpresenting cells such as macrophages (Mfs) and dendritic cells (DCs) is not well characterized.…”
Section: Introductionmentioning
confidence: 99%